2021
DOI: 10.22438/jeb/42/6/mrn-1766
|View full text |Cite
|
Sign up to set email alerts
|

Ethanolic root extract of Rauwolfia serpentina alleviates copper induced genotoxicity and hepatic impairments in spotted snakehead fish, Channa punctatus (Bloch, 1793)

Abstract: Aim: The present study was designed to evaluate the plausible efficacy of ethanolic extract of Rauwolfia serpentina to mitigate copper induced toxicity by investigating cytogenetic biomarkers, i.e., chromosome aberrations (CA) and micronucleus (MN) formation; assessment of biochemical changes in liver enzymes (SGOT, SGPT and ALP) and estimation of protein levels in a freshwater spotted snakehead fish(Channa punctatus). Methodology: The experiment was carried out in six groups, each having 15 specimens for 24,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…As a result of cypermethrin exposure in the testicular tissue of Channa punctatus, clustering and vacuolization among spermatogenic cells in seminiferous tubule and deteriorated spermatids occurred [22]. Staicu et al [23] determined that there was a decrease in sperm count in Corassius auratus gibelio exposed to deltamethrin for 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of cypermethrin exposure in the testicular tissue of Channa punctatus, clustering and vacuolization among spermatogenic cells in seminiferous tubule and deteriorated spermatids occurred [22]. Staicu et al [23] determined that there was a decrease in sperm count in Corassius auratus gibelio exposed to deltamethrin for 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in liver biomarker enzymes, such as ALT, AST, and ALP, is indicative of liver ailments. The activity of ALT, AST, and ALP was thus estimated using the method of Trivedi et al 29,30 TB levels were recorded using the modified method of Perry et al 31 The activity of ALT, AST, and ALP enzymes are represented in IU/L of serum. 32 TB was calculated using the method adopted by Bharti and Rasool.…”
Section: Assessment Of Biochemical Parametersmentioning
confidence: 99%
“…Some studies choose the concentration of copper sulfate as the concentration unit, while others choose the concentration of Cu 2+ as the concentration unit. For example, 4 mg/L of (1/10 dose of LC50) copper sulfate was confirmed to have harmful effects on the fertility of male Nile tilapia [ 10 ], while 0.4 mg/L of Cu 2+ induced genotoxicity and hepatic impairments in spotted snakehead fish [ 11 ]. Meanwhile, studies have demonstrated that a prophylactic bath treatment in copper sulphate has short physical impacts on pikeperch, and the treatment does not significantly impact the health condition of pikeperch [ 12 ].…”
Section: Introductionmentioning
confidence: 99%